Gastroprotective effect of apricot kernel oil in ethanol-induced gastric mucosal injury in rats. (17th November 2018) - Karaboğa, İ. and Ovalı, M. A. and Yılmaz, A. and Alpaslan, M.
ABSTRACT: We investigated the gastroprotective effect of apricot kernel oil on ethanol induced gastric ulcer in rats. Male Wistar albino rats were divided into control, ethanol and apricot kernel oil + ethanol groups. The fatty acid composition of apricot kernel oil was determined using GC-MS. A gastric ulcer index was defined as the area percentage of the gastric mucosa consisting of ulcerated tissue. Gastric tissue was investigated by TUNEL staining for apoptosis, immunohistochemical iNOS staining, measurement of gastric IL-10 and IL-6 expression by ELISA and assays of catalase, malondialdehyde and superoxide dismutase. The ethanol group exhibited a higher gastric ulcer score, increased IL-6 level, increased number of inducible nitric oxide synthase-positive and TUNEL positive cells, and a higher MDA level compared to the control group. The apricot kernel oil + ethanol group exhibited significantly fewer gastric lesions compared to the ethanol group. Apricot kernel oil protects rat gastric mucosa against ethanol induced injury by its anti-inflammatory, anti-oxidative and anti-apoptotic effects, and might be useful for reducing the severity of gastric ulcers.